1998
DOI: 10.1159/000013797
|View full text |Cite
|
Sign up to set email alerts
|

A ‘Neural’ Response with 3-ms Latency Evoked by Loud Sound in Profoundly Deaf Patients

Abstract: A large negative deflection with a latency of 3 ms was observed in the auditory brainstem response (ABR) waveforms of some patients with peripheral profound deafness. This deflection was termed the N3 potential. In this paper, we review patients with the N3 potential and discuss the characteristics of abnomral ABR waveforms. The origin of the N3 potential was also discussed, especially with respect to vestibular evoked potentials. In most of the patients, audiograms showed no response to the maximum output of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
3
25
0
Order By: Relevance
“…6, 8, 13, 15, 18, and 19) presented no N3 potentials, the additional factors may be the main reason for this discrepancy. Kato et al 11 suggested two potential mechanisms for the generation of the N3 potential: a direct potential from the lower brainstem, including the cochlear nuclei 12 or superior olive, 10 and a stationary potential generated when the propagating saccular nerve action potential crosses the conductivity boundaries to the lower brainstem. An additional factor, such as an intact neural pathway from the sacculus to the lower brainstem, may be necessary for generating the N3 potential.…”
Section: Discussionmentioning
confidence: 99%
“…6, 8, 13, 15, 18, and 19) presented no N3 potentials, the additional factors may be the main reason for this discrepancy. Kato et al 11 suggested two potential mechanisms for the generation of the N3 potential: a direct potential from the lower brainstem, including the cochlear nuclei 12 or superior olive, 10 and a stationary potential generated when the propagating saccular nerve action potential crosses the conductivity boundaries to the lower brainstem. An additional factor, such as an intact neural pathway from the sacculus to the lower brainstem, may be necessary for generating the N3 potential.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we recorded a negative deflection in response to STB in the presence of WN with a latency of 3 to 4 ms in subjects with preserved hearing, although Kato et al [1] reported that they recorded an N3 only in patients with peripheral profound deafness. We consider that we were able to record N3 because we applied different recording methods from those in previous studies.…”
Section: Discussionmentioning
confidence: 72%
“…The ABR consist of fast waves and slow waves within 10 ms after the onset of stimulation. Apart from these positive waves, Kato et al [1] reported that a large negative deflection with a latency of 3 ms (N3) could be recorded in patients with peripheral profound deafness. It was suggested that N3 might be of vestibular origin, saccular origin in particular, as is the vestibular evoked myogenic potential (VEMP) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustically evoked V-shaped negative responses at 3-4 ms (N3) are described in profound hearing loss [14,15]. They are suggested to be of saccular origin, but appear much earlier than our potentials.…”
Section: Discussionmentioning
confidence: 97%